A semi-solid lithium manganate battery and a method of manufacturing the same
By in-situ copolymerizing DOPO flame-retardant units and imidazolium groups in a gel electrolyte to form a three-dimensional network structure, the problems of flame-retardant effect decay and low lithium-ion transference number of existing gel electrolytes are solved, thereby improving the safety and stability of lithium-ion batteries.
Patent Information
- Application Number
- CN202611308891.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-08-27
AI Technical Summary
Existing gel electrolyte systems suffer from problems such as flame retardancy decaying with cycling, low lithium ion transference number, significant concentration polarization, and poor long-term stability, especially posing safety hazards in terms of lithium dendrite growth and electrode interface degradation.
A flame-retardant gel electrolyte with a three-dimensional network structure is formed by in-situ copolymerization of polymerizable functional monomers containing DOPO flame-retardant units and imidazolium groups with polyethylene glycol diacrylate and polyethylene glycol methyl ether methacrylate in a liquid electrolyte. The flame-retardant units and imidazolium groups are anchored by covalent bonds, thereby increasing the lithium ion migration number and inhibiting lithium dendrites.
It achieves long-lasting flame retardancy, high lithium-ion transference number and battery safety, reduces the risk of electrolyte leakage and combustion, and improves battery cycle performance and thermal stability.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a semi-solid lithium manganese oxide battery and its preparation method. Background Technology
[0002] Lithium manganese oxide batteries are widely used in electric two-wheelers, low-speed electric vehicles, and energy storage due to their low cost, good rate performance, and relatively high safety. Currently, commercially available lithium manganese oxide batteries generally use liquid carbonate electrolytes, which pose risks of leakage and flammability. Gel polymer electrolytes, by locking in the liquid electrolyte through a polymer network, balance near-liquid ionic conductivity with good safety, representing an important technological route for the transition from liquid batteries to all-solid-state batteries. In-situ polymerization, which involves injecting a precursor solution containing monomers, crosslinking agents, and initiators into the battery cell for internal polymerization and solidification, is compatible with existing liquid battery production lines and provides good contact between the gel and electrode interfaces, attracting widespread attention from the industry. Furthermore, grafting and modifying the polymer monomers to introduce flame-retardant and ion-regulating functional groups is a crucial means to improve the overall performance of semi-solid-state batteries.
[0003] However, existing gel electrolyte systems still have the following shortcomings: First, flame retardant modification often employs physical blending of phosphate ester flame retardants with the electrolyte, resulting in a lack of effective anchoring of small flame retardant molecules. These molecules tend to migrate and precipitate at the electrode interface during cycling, and free phosphorus-containing molecules may decompose and consume active lithium on the negative electrode side, leading to a decline in flame retardant effect with cycling and deteriorating battery cycle performance. Second, in conventional gel electrolytes, anions and lithium ions migrate synchronously, with lithium ion migration numbers typically only 0.3–0.4, resulting in significant concentration polarization, which easily induces lithium dendrite growth and accelerates interface degradation. Third, when using methods that separately add phosphorus-containing flame retardant monomers and ionic monomers for copolymerization, the functional components are dispersed, requiring high doping levels. Furthermore, ionic monomers are often used in the form of chloride salts, and residual chloride ions easily corrode the aluminum current collector, affecting the long-term stability of the battery. Therefore, how to provide a gel electrolyte and semi-solid lithium manganese oxide battery that combines long-lasting flame retardant effect, high lithium ion migration number, and compatibility with existing processes is a pressing technical problem to be solved in this field. Summary of the Invention
[0004] The purpose of this invention is to provide a semi-solid lithium manganese oxide battery and its preparation method, so as to solve the problems existing in the prior art.
[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: A semi-solid lithium manganese oxide battery, the semi-solid lithium manganese oxide battery comprising a positive electrode, a negative electrode, a separator, and a gel electrolyte; By weight, the gel electrolyte comprises 3-8 parts of functional monomer, 2-5 parts of polyethylene glycol diacrylate, 5-15 parts of polyethylene glycol methyl ether methacrylate, 0.1-0.5 parts of initiator, and 80-85 parts of liquid electrolyte; The functional monomer is obtained by PN coupling of DOPO and benzimidazole, followed by quaternization of p-vinylbenzyl chloride and anion exchange with lithium bis(trifluoromethanesulfonyl)imide.
[0006] Further, preferably, the initiator is one or more of azobisisobutyronitrile, dimethyl azobisisobutyrate, azobisisoheptanenitrile, and azobisisovalerate.
[0007] Further, preferably, the liquid electrolyte is a 1M solution formed by dissolving one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, or lithium bis(trifluoromethanesulfonyl)imide in ethylene carbonate, diethyl carbonate, and dimethyl carbonate in a volume ratio of 1:1:1.
[0008] Furthermore, preferably, the liquid electrolyte further includes 3-5% by mass of fluoroethylene carbonate as an interfacial film-forming additive.
[0009] A method for preparing a semi-solid lithium manganese oxide battery, applicable to any of the semi-solid lithium manganese oxide batteries described above, wherein the semi-solid lithium manganese oxide battery includes the following preparation steps: Mix 3-8 parts of functional monomer, 2-5 parts of polyethylene glycol diacrylate, 5-15 parts of polyethylene glycol methyl ether methacrylate, 0.1-0.5 parts of initiator with 80-85 parts of liquid electrolyte, stir evenly and inject into battery casing, react at 60-65℃ under nitrogen atmosphere for 2-4 hours to obtain gel electrolyte, thus obtaining semi-solid lithium manganese oxide battery.
[0010] Further, preferably, the functional monomer comprises the following preparation steps: adding a quaternary ammonium salt intermediate to deionized water at 8-12 times the mass of the quaternary ammonium salt intermediate, then adding lithium bis(trifluoromethanesulfonyl)imide at 0.6-0.7 times the mass of the quaternary ammonium salt intermediate, and reacting at a temperature of 25-35°C for 12-24 hours; after the reaction is completed, washing with deionized water 3-5 times, filtering, and vacuum drying the product at 40-50°C to obtain the functional monomer.
[0011] Further, preferably, the quaternary ammonium salt intermediate includes the following preparation steps: adding the intermediate to acetonitrile at 15-20 times its mass, then adding 0.1%-0.3% hydroquinone at the mass of the intermediate, mixing evenly, and then adding a 20%-30% p-vinylbenzylchloroacetonitrile solution dropwise at a temperature of 75-85°C under a nitrogen atmosphere. After the addition is complete, react at a temperature of 75-85°C for 24-48 hours; after the reaction is completed, cool to 25-35°C, add the reaction solution to 25-30 times its mass of diethyl ether to precipitate, filter, wash the precipitate with diethyl ether 3-5 times, and dry to obtain the quaternary ammonium salt intermediate.
[0012] Further, preferably, the intermediate comprises the following preparation steps: adding DOPO to acetonitrile at 15-20 times the mass of DOPO, then adding triethylamine at 1.2-1.5 times the mass of DOPO, mixing thoroughly, then adding sulfonyl chloride at 0.6-0.7 times the mass of DOPO dropwise under a nitrogen atmosphere at a temperature of 0-5°C, reacting at 25-35°C for 0.5-1 h, then adding benzimidazole at 0.5-0.6 times the mass of DOPO, and reacting at 80-85°C under a nitrogen atmosphere for 6-12 h; after the reaction is completed, cooling to 25-35°C, filtering, and removing the solvent from the filtrate under reduced pressure, then recrystallizing with ethanol, filtering, and drying the filtered product to obtain the intermediate.
[0013] Further, preferably, the mass ratio of p-vinylbenzyl chloride to the intermediate is 0.45~0.55:1.
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: This technical solution employs polymerizable functional monomers containing DOPO flame-retardant units and imidazolium groups, which are in-situ copolymerized with polyethylene glycol diacrylate and polyethylene glycol methyl ether methacrylate in a liquid electrolyte to form a flame-retardant gel electrolyte with a three-dimensional network structure. In existing technologies, flame retardants are mostly added through physical blending, which can easily migrate and precipitate at the electrode interface during cycling. Free DOPO may also decompose on the negative electrode side, consuming active lithium, and the flame-retardant effect decreases with cycling. Conventional gel electrolytes typically have a lithium-ion transference number of only 0.3–0.4, resulting in significant concentration polarization. Liquid electrolytes also pose safety risks due to flammability and leakage. In this scheme, functional monomers are covalently integrated into the three-dimensional gel network via in-situ copolymerization of vinylbenzyl double bonds. The flame-retardant units and imidazolium groups are anchored to the polymer backbone, making them less prone to migration and failure during cycling. The imidazolium cations bind electrolyte anions, increasing the lithium-ion transference number to 0.67~0.7, which helps suppress concentration polarization and lithium dendrites. The three-dimensional network locks about 80% of the liquid electrolyte inside the gel, maintaining an ionic conductivity of 1.58~1.71 mS / cm, while reducing the risk of electrolyte leakage and combustion. This method integrates polymerizable double bonds, an imidazolium ring, a PN-coupled DOPO unit, and a TFSI⁻ pair of anions within a single molecule. Compared to copolymerization methods that separately add phosphorus-containing flame-retardant monomers and ionic monomers, this approach offers more concentrated functionality and lower doping levels. DOPO is PN-coupled to the nitrogen atom of benzimidazole. Upon heating, it releases PO· radicals in the gas phase to quench combustion chain radicals and catalyzes char formation in the condensed phase matrix. It forms a PN synergistic effect with the nitrogen-containing ring, resulting in good flame-retardant efficiency. The imidazolium ring and DOPO share the same side chain, achieving both increased migration number and flame-retardant effect at lower doping levels. The fused-ring rigid segments of benzimidazole and DOPO contribute to improved thermal and dimensional stability of the gel. The electrochemically stable and weakly coordinated TFSI⁻ pair of anions ensures the solubility of the functional monomers in carbonate electrolytes. In summary, this technical solution synthesizes functional monomers with flame retardancy, anion anchoring, and polymerizability through molecular design, and prepares flame-retardant gel electrolytes and semi-solid lithium manganese oxide batteries through in-situ copolymerization with acrylate monomers and liquid electrolytes. In this system, the three-dimensional gel network provides a confined matrix for the electrolyte and functional groups, imidazolium anchors anions to increase lithium-ion transference number, and DOPO, after PN coupling grafting, enhances battery safety through the synergistic effect of gas-phase free radical quenching and condensed phase carbonization. Detailed Implementation
[0015] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0016] Example 1 S1. Add DOPO to acetonitrile at 15 times its mass, then add triethylamine at 1.2 times its mass, mix well, and then add sulfonyl chloride at 0°C under a nitrogen atmosphere dropwise. After the addition is complete, react at 25°C for 0.5 h, then add benzimidazole at 0.5 times its mass, and react at 80°C under a nitrogen atmosphere for 6 h. After the reaction is complete, cool to 25°C, filter, and evaporate the solvent from the filtrate under reduced pressure. Then add ethanol to recrystallize, filter, and dry the filtered product to obtain the intermediate. S2. Add the intermediate to acetonitrile at 15 times its mass, then add 0.1% hydroquinone (by mass of the intermediate), mix thoroughly, and then add a 20% (by mass) solution of p-vinylbenzyl chloride acetonitrile dropwise at 75°C under a nitrogen atmosphere. After the addition is complete, react at 75°C for 24 hours. After the reaction is complete, cool to 25°C, add the reaction solution to ether at 25 times its mass, precipitate, filter, wash the precipitate three times with ether, and dry to obtain the quaternary ammonium salt intermediate. The mass ratio of p-vinylbenzyl chloride to the intermediate is 0.45:1. S3. Add the quaternary ammonium salt intermediate to deionized water at 8 times its mass, and then add lithium bis(trifluoromethanesulfonyl)imide at 0.6 times its mass. React at 25°C for 12 hours. After the reaction is complete, wash with deionized water three times, filter, and dry the product under vacuum at 40°C to obtain the functional monomer.
[0017] Example 2 S1. Add DOPO to acetonitrile at 17.5 times its mass, then add triethylamine at 1.35 times its mass, mix well, and then add sulfonyl chloride at 0.65 times its mass, under a nitrogen atmosphere at 2°C. After the addition is complete, react at 30°C for 0.75 h, then add benzimidazole at 0.55 times its mass, and react at 80°C under a nitrogen atmosphere for 9 h. After the reaction is complete, cool to 30°C, filter, and evaporate the solvent from the filtrate under reduced pressure. Then add ethanol to recrystallize, filter, and dry the filtered product to obtain the intermediate. S2. The intermediate was added to acetonitrile at 17.5 times its mass, followed by 0.2% hydroquinone at 0.2% of its mass. The mixture was thoroughly mixed, and then a 25% (w / w) solution of p-vinylbenzyl chloride acetonitrile was added dropwise at 80°C under a nitrogen atmosphere. After the addition was complete, the mixture was reacted at 80°C for 36 hours. After the reaction was completed, the mixture was cooled to 30°C, and the reaction solution was added to ether at 27.5 times its mass, followed by precipitation. The precipitate was filtered, washed four times with ether, and dried to obtain the quaternary ammonium salt intermediate. The mass ratio of p-vinylbenzyl chloride to the intermediate was 0.5:1. S3. Add the quaternary ammonium salt intermediate to deionized water at 10 times its mass, and then add lithium bis(trifluoromethanesulfonyl)imide at 0.65 times its mass. React at 30°C for 18 hours. After the reaction is complete, wash with deionized water four times, filter, and vacuum dry the product at 45°C to obtain the functional monomer.
[0018] Example 3 S1. Add DOPO to acetonitrile at 20 times its mass, then add triethylamine at 1.5 times its mass, mix well, and then add sulfonyl chloride at 0.7 times its mass, under a nitrogen atmosphere at 5°C. After the addition is complete, react at 35°C for 1 hour, then add benzimidazole at 0.6 times its mass, and react at 85°C under a nitrogen atmosphere for 12 hours. After the reaction is complete, cool to 35°C, filter, and evaporate the solvent from the filtrate under reduced pressure. Then add ethanol to recrystallize, filter, and dry the filtered product to obtain the intermediate. S2. The intermediate was added to acetonitrile in a volume 20 times its weight, followed by 0.3% hydroquinone (by weight of the intermediate). The mixture was thoroughly mixed, and then a 30% (by weight) solution of p-vinylbenzyl chloride acetonitrile was added dropwise at 85°C under a nitrogen atmosphere. After the addition was complete, the mixture was reacted at 85°C for 48 hours. After the reaction was completed, the mixture was cooled to 35°C, and the reaction solution was added to ether in a volume 30 times its weight of the intermediate to precipitate the product. The precipitate was filtered, washed five times with ether, and dried to obtain the quaternary ammonium salt intermediate. The mass ratio of p-vinylbenzyl chloride to the intermediate was 0.55:1. S3. Add the quaternary ammonium salt intermediate to deionized water at 12 times its mass, and then add lithium bis(trifluoromethanesulfonyl)imide at 0.7 times its mass. React at 35°C for 24 hours. After the reaction is complete, wash with deionized water 5 times, filter, and dry the product under vacuum at 50°C to obtain the functional monomer.
[0019] Example 4 S10. Preparation of precursor solution: Take 80g of basic electrolyte (a 1M solution formed by dissolving lithium bis(trifluoromethanesulfonyl)imide in ethylene carbonate, diethyl carbonate and dimethyl carbonate in a volume ratio of 1:1:1, and adding 4% fluoroethylene carbonate as an interfacial film-forming additive, and mixing evenly) at room temperature, add 5g of the functional monomer prepared in Example 1, 3g of crosslinking agent polyethylene glycol diacrylate, 12g of polyethylene glycol methyl ether methacrylate and 0.3g of initiator azobisisobutyronitrile, stir evenly to obtain a colorless and transparent precursor solution; S20, Liquid Injection, Primary Formation, Degassing, and Aging: The positive electrode (lithium manganese oxide: conductive carbon black: polyvinylidene fluoride = 94:3:3, coated on aluminum foil, rolled and cut), the negative electrode (graphite: conductive carbon black: sodium carboxymethyl cellulose: styrene-butadiene rubber = 94.5:1.5:1.5:2.5, coated on copper foil), and the separator are stacked, tab welded, and packaged in an aluminum-plastic film to form a dry cell. The dry cell is thoroughly dried by baking at 85℃ and a vacuum of -95kPa for 24 hours, then injected with the aforementioned precursor solution. After injection, it is left to stand at room temperature for 24 hours to allow the precursor to fully wet the electrode and separator. Subsequently, primary formation, degassing, and aging are performed. Primary formation is carried out at a current of 0.05C for 5 hours; degassing is then performed at a vacuum of -98kPa for 5 seconds; the aging temperature is 40℃ for 36 hours. S30, in-situ thermal polymerization: The battery cell obtained by S20 is placed at 65℃ for 3 hours. During polymerization, 0.1~0.3MPa hot pressure is applied to ensure that the gel adheres to the electrode interface and the electrolyte gel is solidified to form a gel electrolyte. S40, Secondary Formation and Capacity Testing: The cells obtained from S30 are subjected to secondary formation at a current of 0.2C, with a charging cutoff voltage of 4.2V; then, venting is performed at a vacuum degree of -98kPa for 5s; and then, after conventional capacity testing, a semi-solid lithium manganese oxide battery is obtained.
[0020] Example 5 The only difference from Example 4 is step S10: the functional monomer prepared in Example 1 is replaced with the functional monomer prepared in Example 2.
[0021] Example 6 The only difference from Example 4 is step S10: the functional monomer prepared in Example 1 is replaced with the functional monomer prepared in Example 3.
[0022] Example 7 The only difference from Example 4 is step S10: the functional monomer prepared in Example 1 is replaced with the intermediate prepared in Example 2.
[0023] Example 8 The only difference from Example 4 is step S10: the functional monomer prepared in Example 1 is replaced with the quaternary ammonium salt intermediate prepared in Example 2.
[0024] Example 9 The only difference from Example 4 is step S10: the functional monomer prepared in Example 1 is not added; The batteries prepared in Examples 4 to 9 above were subjected to cycle performance testing, safety performance testing, ion conductivity testing, lithium ion transference number testing, and flame retardant performance testing.
[0025] (1) Cyclic performance test: Using a Blue Electric charge-discharge tester, at room temperature of 25℃, the battery is charged at a constant current of 0.5C to 4.2V, then charged at a constant voltage of 4.2V to a current of 0.05C, and then discharged at a constant current of 1C to 2.5V. The discharge capacity of the first cycle is recorded as C0. The above steps are repeated for 1000 cycles, and the discharge capacity of the 1000th cycle is recorded as C1. Then, the cycle capacity retention rate after 1000 cycles = (C1 / C0) × 100%.
[0026] (2) Safety performance test: After the battery is fully charged, place the battery on a flat heating device with its surface in direct contact with the battery surface. Heat the sample continuously at 300W until thermal runaway occurs or the temperature at the monitoring point reaches 300℃. Then turn off the heating device and observe for 1 hour, recording whether there is smoke, fire or electrolyte leakage.
[0027] (3) Ionic conductivity test: The battery cell was placed in a 65℃ oven for 3 hours to react and solidify the electrolyte gel. The bulk impedance Rb was measured by AC impedance method (frequency range 0.1Hz~1MHz, AC amplitude 5mV), and the gel film thickness L and steel sheet area S were measured. The ionic conductivity was calculated according to the formula σ=L / (Rb×S).
[0028] (4) Lithium-ion transference number test: Apply a constant polarization voltage of 10mV to the battery, record the initial current I0 and the steady-state current Iss, and test the interface impedances R0 and Rss before and after polarization respectively. Calculate the lithium-ion transference number according to the formula tLi=Iss(ΔV-I0*R0) / I0(ΔV-Iss*Rss).
[0029] Table 1 Performance Test Results As shown in Table 1, the semi-solid lithium manganese oxide batteries (Examples 4-6) prepared using the functional cells of this invention have excellent and stable comprehensive performance: after 1000 cycles, the capacity retention rate is as high as 90.8%~92.3%, the ionic conductivity reaches 1.58~1.71 mS / cm, the lithium ion transference number is 0.67~0.7, and there is no smoke, no fire, and no electrolyte leakage during safety performance tests.
[0030] Compared with Examples 4-6, in Example 7, only the intermediate of DOPO and benzimidazole coupled via PN was added to the precursor. Since this intermediate does not contain polymerizable double bonds, it cannot be chemically bonded to the gel network through in-situ polymerization and can only exist in the form of free small molecules. During cycling, it is easy to migrate, aggregate and undergo side reactions on the negative electrode side. At the same time, because it is not quaternized, it does not have an imidazolium anion anchoring structure. Its cycling capacity retention, ionic conductivity and lithium ion transference number dropped significantly to 76.4%, 0.83 mS / cm and 0.42, respectively. The flame retardant effect was also significantly weakened, and slight smoke appeared. In Example 8, a quaternary ammonium salt intermediate without anion exchange was used. Although the polymerizable double bond and imidazolium structure were retained, and the flame retardant performance and migration number were basically maintained, the residual chloride ions corroded the aluminum current collector under a full charge of 4.2V and triggered interfacial side reactions, resulting in a decrease in cycle capacity retention to 82.7% and ionic conductivity to 1.29 mS / cm. In Example 9, no functional monomers were added, and the gel electrolyte contained neither anionic anchoring sites nor flame-retardant components. The lithium-ion migration number was only 0.39, and smoke, fire, and electrolyte leakage occurred during the safety performance test.
[0031] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the present invention.
Claims
1. A semi-solid lithium manganese oxide battery, characterized in that, The semi-solid lithium manganese oxide battery includes a positive electrode, a negative electrode, a separator, and a gel electrolyte; By weight, the gel electrolyte comprises 3-8 parts of functional monomer, 2-5 parts of polyethylene glycol diacrylate, 5-15 parts of polyethylene glycol methyl ether methacrylate, 0.1-0.5 parts of initiator, and 80-85 parts of liquid electrolyte; The functional monomer is obtained by PN coupling of DOPO and benzimidazole, followed by quaternization of p-vinylbenzyl chloride and anion exchange with lithium bis(trifluoromethanesulfonyl)imide.
2. The semi-solid lithium manganese oxide battery according to claim 1, characterized in that, The initiator is one or more of azobisisobutyronitrile, dimethyl azobisisobutyrate, azobisisoheptanenitrile, and azobisisovalerate.
3. The semi-solid lithium manganese oxide battery according to claim 1, characterized in that, The liquid electrolyte is a 1M solution formed by dissolving one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, or lithium bis(trifluoromethanesulfonyl)imide in ethylene carbonate, diethyl carbonate, and dimethyl carbonate in a volume ratio of 1:1:
1.
4. The semi-solid lithium manganese oxide battery according to claim 1, characterized in that, The liquid electrolyte also includes 3-5% fluoroethylene carbonate as an interfacial film-forming additive.
5. A method for preparing a semi-solid lithium manganese oxide battery, applicable to the semi-solid lithium manganese oxide battery described in any one of claims 1 to 4, characterized in that, The semi-solid lithium manganese oxide battery includes the following preparation steps: Mix 3-8 parts of functional monomer, 2-5 parts of polyethylene glycol diacrylate, 5-15 parts of polyethylene glycol methyl ether methacrylate, 0.1-0.5 parts of initiator with 80-85 parts of liquid electrolyte, stir evenly and inject into battery casing, react at 60-65℃ under nitrogen atmosphere for 2-4 hours to obtain gel electrolyte, thus obtaining semi-solid lithium manganese oxide battery.
6. The method for preparing a semi-solid lithium manganese oxide battery according to claim 5, characterized in that, The functional monomer comprises the following preparation steps: adding a quaternary ammonium salt intermediate to deionized water at 8-12 times its mass, then adding lithium bis(trifluoromethanesulfonyl)imide at 0.6-0.7 times its mass, and reacting at 25-35°C for 12-24 hours; after the reaction is completed, washing with deionized water 3-5 times, filtering, and vacuum drying the product at 40-50°C to obtain the functional monomer.
7. The method for preparing a semi-solid lithium manganese oxide battery according to claim 6, characterized in that, The quaternary ammonium salt intermediate comprises the following preparation steps: adding the intermediate to acetonitrile at 15-20 times its mass, then adding 0.1%-0.3% hydroquinone at the mass of the intermediate, mixing thoroughly, and then adding a 20%-30% p-vinylbenzylchloroacetonitrile solution dropwise under a nitrogen atmosphere at a temperature of 75-85℃. After the addition is complete, the reaction is carried out at a temperature of 75-85℃ for 24-48 hours. After the reaction is completed, the mixture is cooled to 25-35℃, and the reaction solution is added to 25-30 times its mass of diethyl ether to precipitate the product. The product is filtered, washed with diethyl ether 3-5 times, and dried to obtain the quaternary ammonium salt intermediate.
8. The method for preparing a semi-solid lithium manganese oxide battery according to claim 7, characterized in that, The intermediate comprises the following preparation steps: DOPO is added to acetonitrile at 15-20 times its mass, followed by triethylamine at 1.2-1.5 times its mass, and mixed thoroughly. Then, under a nitrogen atmosphere at a temperature of 0-5°C, sulfonyl chloride at 0.6-0.7 times its mass, is added dropwise. After the addition is complete, the mixture is reacted at 25-35°C for 0.5-1 h. Subsequently, benzimidazole at 0.5-0.6 times its mass, is added, and the mixture is reacted at 80-85°C under a nitrogen atmosphere for 6-12 h. After the reaction is completed, the mixture is cooled to 25-35°C, filtered, and the solvent is removed by vacuum distillation of the filtrate. Ethanol is then added for recrystallization, followed by filtration and drying of the filtered product to obtain the intermediate.
9. The method for preparing a semi-solid lithium manganese oxide battery according to claim 7, characterized in that, The mass ratio of p-vinylbenzyl chloride to the intermediate is 0.45~0.55:1.
Citation Information
Patent Citations
Flame-retardant in-situ polymerization gel electrolyte battery and preparation method thereof
CN119153771A
Electrolyte, electrolyte composition, and those application
JP2010192226A
